A critical analysis of 20th century modern terrace housing in Malaysia - Utaberta, Nangkula; Nik Ramzi Shah, Nik Farah Elina; Mohd Rasdi, Mohd Tajuddin; Othuman Mydin, Md Azree (Trans Tech Publications, 2015)
The development of architecture in early housing in Malaysia existed in the form of shop house and terrace house which were being introduced and popularized by Chinese migrants who settled in Malaysia before the Colonization by British Empire. This paper will discuss briefly the development of modern terrace house in Malaysia. Terrace house is define as a typology of one storey middle class terrace house in this country based on the existing literature review and our research. Those typologies will be used later for the process of typological assessment of terrace house from the cultural perspective at the end of the research. Thus, this paper is important as a step to understand the early development of terrace houses and to see how far the evolution of terrace houses happened until today.